The Influence of Format Readability on Children's Reading Speed and Comprehension - Stephanie L. Day; Nilsu Atilgan; Amy E. Giroux; Ben D. Sawyer (MDPI AG, 2024)
Background: Format readability, including font and spacing, impacts reading metrics in adults, but will the research generalize to children? We examined how eight fonts (four serif and four sans serif) and three-character spacing variations influenced children's reading comprehension and reading speed. Methods: Fifty-one students in third-fifth grade read 11 narrative text passages on a computer and answered comprehension questions. Passages were randomized in terms of order. First, the font in which the text of each passage was presented was manipulated. Then passages were presented in three spacing manipulations (narrow, normal, and wide). Results: A linear mixed effects model demonstrated that, on a group-level, passages presented in Roboto and Arial font were read significantly faster (words-per-minute) than other fonts. On the individual level, students experienced significant boosts in reading speed (words-per-minute) between their best and worst fitting font, and spacing. A chi-square test showed no one font or spacing setting that was most likely to be a students' font fit or clash. For reading comprehension, no speed-comprehension tradeoff was observed. Conclusions: Changes to text format at the group and individual level may yield boosts in reading speed for students, without negatively impacting reading comprehension.